THE DESIGN OF BANDUNG STATION AREA THROUGH WALKABILITY USING URBAN NETWORK ANALYSIS - Abdul Soleh, Muhammad
Walkability is a component of a liveable city, then a liveable city will be able to improve the quality of life and encourage sustainable urban activities. Bandung city through RTRW 2011 – 2031 document began to direct the construction and development of its city to be more walkable by making the pedestrians network a liaison between activity centers and not as a focus for regional growth. This research aims to investigate the relationship between the characteristics of the built environment on pedestrians in influencing the movement patterns and activities of pedestrians. Urban Network Analysis (UNA) is a software toolbox in software ArcGIS that can be used to explain spatial relationships in a built environment network. These spatial relationships include circulation routes, corridors, and roads or connecting infrastructure. As a quantitative approach, UNA predicts travel volume, route choice, assessment of infrastructure utilization so that people can walk and cycle comfortably. The analysis carried out through UNA toolbox require three main data inputs, namely, 1) network; 2) origin; and 3) destination. The research was conducted at a 900-meter radius in the Bandung Station area by conducting two simulations of the existing conditions and post-design conditions. The result of UNA simulation shows that spatial characteristic of the area (urban design elements) has an influence on pedestrian movement patterns. Land use and building mass intensity as well as regional circulation patterns have an influence on the accessibility index (reach index, gravity index, and straightness index) of an area. Meanwhile, the block pattern, the character of the building, and the character of the road network have an influence on the number of trips in a corridor or intersection (betweenness index) and determine the level of isolation of a building (closeness index). By elaborating the results of the UNA analysis and urban design elements, this research can determine the effect of urban design elements on foot movement patterns and how planning and design can form a pedestrian-friendly area.